2018
DOI: 10.1016/j.heliyon.2018.e00573
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microcystin contamination in blue-green algal dietary supplements using a protein phosphatase inhibition-based test kit

Abstract: The cyanobacterium Aphanizomenon flos-aquae (AFA), from Upper-Klamath Lake, Oregon, are used to produce blue-green algal (BGA) dietary supplements. The periodic co-occurrence of hepatotoxin-producing contaminant species prompted the Oregon Health Division to establish a limit of 1 μg/g microcystin (MC) for products sold in Oregon in 1997. At the federal level, the current good manufacturing practice (CGMP) regulations for dietary supplements require manufacturers establish a specification, and test, for limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…The presence of microcystin in microalgae-based food supplements has been previously documented, especially when they contain Aphanizomenon [ 6 , 21 , 27 , 28 , 33 , 35 , 45 , 46 ]. The more commercialized Aphanizomenon comes from Klamath Lake (USA), and several reports about the toxicity of this product are found in literature [ 28 , 29 , 30 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of microcystin in microalgae-based food supplements has been previously documented, especially when they contain Aphanizomenon [ 6 , 21 , 27 , 28 , 33 , 35 , 45 , 46 ]. The more commercialized Aphanizomenon comes from Klamath Lake (USA), and several reports about the toxicity of this product are found in literature [ 28 , 29 , 30 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microalgae from other taxonomic groups are also frequently consumed, of which the most popular are probably Chlorella and Haematococcus (Trebouxiophyceae and Chlorophyceae, respectively). These products are available in diverse forms (e.g., pills, capsules, powder, flakes, tablets) [ 19 , 20 , 21 ] and have been progressively included in other products, like biscuits, pasta, drinks or yoghurt [ 22 , 23 ]. As it is compulsory to only indicate the composition, daily intake and a warning about them not substituting healthy diet in most countries [ 24 , 25 ], the labels of these products are often inaccurate and do not offer information about geographic origin, if they are collected from nature, or if they are produced in close bioreactors or open systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein phosphatase inhibition assays and immunoassays are suitable substitutions for rapid detection of MC-LR because of its potency to inhibit the activities of protein phosphatases 1 and 2A (PPl, PP2A) as a similar manner to okadic acid [18,19], where the former methods are sensitive than later due to the provision of insight on toxicology [2]. Like MC-LR, other MC variants are also involving the potent inhibition of protein phosphatases and, therefore, PPIA has been used for the determination of MC contamination [20]. These assays are considered as the ideal toxicity assays for MC determination in the environmental samples [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It is important for DNA synthesis and takes part in hemoglobin production [23,27]. A recent study reported that in the United States, numerous dietary supplements containing cyanobacterial species such as Aphanizomenon flos-aquae, Spirulina, and chlorophyte Chlorella are available in the consumer markets [28]. Microcystis and Oscillatoria are also present at the source; both these genera are known to produce microcystins and nodularins (toxic cyclic peptides) that can contaminate the raw materials.…”
Section: Nutrition/food Supplementmentioning
confidence: 99%